2022
DOI: 10.1126/sciadv.abl6848
|View full text |Cite
|
Sign up to set email alerts
|

Head direction cells in a migratory bird prefer north

Abstract: Animals exhibit remarkable navigation abilities as if they have an internal compass. Head direction (HD) cells encoding the animal’s heading azimuth are found in the brain of several animal species; the HD cell signals are dependent on the vestibular nuclei, where magnetic responsive cells are present in birds. However, it is difficult to determine whether HD cell signals drive the compass orientation in animals, as they do not necessarily rely on the magnetic compass under all circumstances. Recording of HD c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Head direction cells (Taube et al, 1990a,b), grid cells (Sargolini et al, 2006), border cells (Sargolini et al, 2006), speed cells (Kropff et al, 2015) and vector trace cells (Poulter et al, 2021) all contribute to the formation of a cognitive map in mammals. In birds, hippocampal place cells (Payne et al, 2021) and head direction cells (Ben-Yishay et al, 2021;Takahashi et al, 2022) have also been recently found. Payne et al (2021) found place cells in two different species of bird: tufted titmice (Baeolophus bicolor) and zebra finches (Taeniopygia guttata).…”
Section: Introductionmentioning
confidence: 96%
“…Head direction cells (Taube et al, 1990a,b), grid cells (Sargolini et al, 2006), border cells (Sargolini et al, 2006), speed cells (Kropff et al, 2015) and vector trace cells (Poulter et al, 2021) all contribute to the formation of a cognitive map in mammals. In birds, hippocampal place cells (Payne et al, 2021) and head direction cells (Ben-Yishay et al, 2021;Takahashi et al, 2022) have also been recently found. Payne et al (2021) found place cells in two different species of bird: tufted titmice (Baeolophus bicolor) and zebra finches (Taeniopygia guttata).…”
Section: Introductionmentioning
confidence: 96%
“…Consequently, their brain constantly compares the current heading direction with the goal direction (Dacke and el Jundi, 2018; Honkanen et al, 2019). While the former is encoded by evolutionarily conserved head-direction (HD) neurons found in different species (Beetz et al, 2022; Ben-Yishay et al, 2021; Geva-Sagiv et al, 2015; Hulse and Jayaraman, 2020; Petrucco et al, 2022; Seelig and Jayaraman, 2015; Takahashi et al, 2022; Taube et al, 1990; Varga and Ritzmann, 2016; Vinepinsky et al, 2020), goal-direction (GD) neurons whose action potential rate correlates with the animal’s goal direction have only been reported in the mammalian brain (Sarel et al, 2017). However, even in the tiny brain of an insect, a robust representation of the goal direction is of the highest ecological importance.…”
Section: Introductionmentioning
confidence: 99%
“…In birds, which require good spatial memory to migrate and locate pertinent environmental cues, neural and genetic studies have been performed on black-capped chickadees ( Poecile atricapillus , Pravosudov et al, 2012 , 2013 ; Croston et al, 2015 ), homing pigeons ( Columba livia , Bingman et al, 2003 ; Gagliardo et al, 2014 ; Herold et al, 2015 ), and a growing body of data collected in domestic chicks ( Gallus gallus , Tommasi et al, 2012 ; Mayer et al, 2018 ; Morandi-Raikova et al, 2020 ). There are also studies in the tufted titmouse ( Baeolophus bicolor , Payne et al, 2021 ), quail ( Coturnix japonica , Ben-Yisahay et al, 2021 ), zebra finch ( Taeniopygia guttata , Mayer et al, 2013 ), and the streaked shearwater ( Calonectris leucomelas , Takahashi et al, 2022 ). In summary, all findings to date have supported the key role of the hippocampal formation in underlying spatial behaviors in birds.…”
Section: Introductionmentioning
confidence: 99%
“…A potentially fifth type, the “head-direction” cell, is documented in both rats ( Rolls, 1999 ) as well as several species of birds outside of homing pigeons. Streaked shearwater demonstrate strong compass-dependent responses predominantly to magnetic north, suggesting that migration is a salient cue for navigation in that species ( Takahashi et al, 2022 ). In another recent study performed in the Japanese quail, head-directional tuning was found in about 12% of HF neurons, with preferred directions spanning all compass directions ( Ben-Yisahay et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%